2003
DOI: 10.1023/b:vlsi.0000003028.71666.44
|View full text |Cite
|
Sign up to set email alerts
|

Robust Numerical Features for Description and Classification of Subcellular Location Patterns in Fluorescence Microscope Images

Abstract: Abstract. The ongoing biotechnology revolution promises a complete understanding of the mechanisms by which cells and tissues carry out their functions. Central to that goal is the determination of the function of each protein that is present in a given cell type, and determining a protein's location within cells is critical to understanding its function. As large amounts of data become available from genome-wide determination of protein subcellular location, automated approaches to categorizing and comparing … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
116
0

Year Published

2005
2005
2017
2017

Publication Types

Select...
7
1
1

Relationship

6
3

Authors

Journals

citations
Cited by 112 publications
(117 citation statements)
references
References 16 publications
1
116
0
Order By: Relevance
“…Excellent work has been done in this field in recent years [46][47][48] . Some researchers write custom software or macros for non-high-throughput image analysis programs, but their general applicability is limited 8,13,24,40,42,[49][50][51][52][53][54][55][56][57] .…”
Section: Image Analysismentioning
confidence: 99%
“…Excellent work has been done in this field in recent years [46][47][48] . Some researchers write custom software or macros for non-high-throughput image analysis programs, but their general applicability is limited 8,13,24,40,42,[49][50][51][52][53][54][55][56][57] .…”
Section: Image Analysismentioning
confidence: 99%
“…The results of one such experiment are shown in Figure 2, where the computer achieves 92% accuracy classifying ten location classes [23], while the human interpreter can only achieve 83% [24]. In another classification study, on the problem of cell detection, it was observed that computers perform comparably to a medium-quality expert, but were still outperformed by an experienced expert.…”
Section: Supervised Classificationmentioning
confidence: 89%
“…However, we have previously proposed that unsupervised methods are more appropriate to the analysis of protein subcellular location patterns [4]. We have used the retroviral CD-tagging technology developed by Jarvik, Berget and colleagues [12] to collect increasing numbers of images of mouse 3T3 cells expressing proteins randomly-tagged with GFP and then cluster them into Subcellular Location Trees [6,13,14].…”
Section: Learning Subcellular Patterns Using Cluster Analysis: Subcelmentioning
confidence: 99%
“…The large volume of images generated by high throughput systems requires automated systems for interpretation. Automated systems not only can recognize all major subcellular patterns [1][2][3], but they can perform as well or better than visual inspection [4][5][6]. Examples of major patterns used for development and testing of these systems are shown in Figure 1.…”
Section: Introductionmentioning
confidence: 99%